1986
DOI: 10.2307/1242126
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Well Depth and Land Quality on the Choice of Irrigation Technology

Abstract: This paper introduces a framework to study the effects of farm characteristics (land quality and well depth) and irrigation technology characteristics (application effectiveness and pressurization requirement) on a farmer's choice of irrigation system. Conditions indicating how the adoption of drip or sprinkler irrigation affects water and energy demands are presented as well as conditions under which these technologies are likely to be adopted. Two functional forms for the production function (quadratic and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
0
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(135 citation statements)
references
References 1 publication
9
119
0
7
Order By: Relevance
“…Similar types of responses were considered in an analysis of household water demand by Lund [1995], where a household's adaptations to shortages in water supply are decomposed into long-run changes in capital stock and short-run changes in management, such as installing a low-flush toilet and taking shorter showers, respectively. Previous studies have shown that an increase in water price leads to the adoption of precision (water conserving) irrigation systems by farmers [Caswell and Zilberman, 1986;Kanazawa, 1992;Green et al, 1996]. This research also shows that the relative profitability of different types of irrigation technologies is conditional on land quality characteristics.…”
Section: Empirical Modelsupporting
confidence: 57%
“…Similar types of responses were considered in an analysis of household water demand by Lund [1995], where a household's adaptations to shortages in water supply are decomposed into long-run changes in capital stock and short-run changes in management, such as installing a low-flush toilet and taking shorter showers, respectively. Previous studies have shown that an increase in water price leads to the adoption of precision (water conserving) irrigation systems by farmers [Caswell and Zilberman, 1986;Kanazawa, 1992;Green et al, 1996]. This research also shows that the relative profitability of different types of irrigation technologies is conditional on land quality characteristics.…”
Section: Empirical Modelsupporting
confidence: 57%
“…Caswell & Zilberman (1985) used a multinomial logit model of three irrigation technology groups to demonstrate that water price policies could induce adoption of water-conserving irrigation technologies for perennial crop growers in the San Joaquin Valley of California. Caswell & Zilberman (1986) demonstrated theoretically the importance of field/soil characteristics (land quality) and well depth in the producer field-level irrigation technology decision. Lichtenberg (1989) used county-level, cross-section/time series data and multinomial logit analysis to determine the importance of centre-pivot irrigation technology in explaining the shift in crop production for western Nebraska to more water-sensitive crops (particularly maize).…”
Section: Methods and Model Presentationmentioning
confidence: 99%
“…When the input in question is a stock resource, technological advancement implies that the resource will be depleted at a faster rate. 1 It is, therefore, important for anyone whose responsibilities include resource management to understand the process by which technology is adopted by potential users and spreads through a population.…”
Section: Introductionmentioning
confidence: 99%
“…Adoption occurs when an individual chooses to accept and use the new technology. The decision to adopt can be thought of as an economic choice, where individuals seek to maximize utility or profits [1][2][3][4]. Individuals adopt a new innovation if it increases their net revenue from production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation